Age-dependent Changes in Dynamic Body Balance as Evaluated by the Body Tracking Test (BTT) - Oda, Makoto; Miyake, Takanori; Yoshida, Tomoe; Yamamoto, Masahiko; Orihara, Hiromi; Osafune, Hirotaka (Nippon Jibi Inkoka Gakkai Kaiho, 1999)
Stability of Posture and gait decays with aging. In this study, we constructed the Body Tracking Test (BTT), to evaluate dynamic body balance function as opposed to static balance. Healthy volunteers of various ages (total, 272 persons) were subjects of the study. The principle of the BTT was for the subject to attempt to track an optical moving target displayed on a computer screen by shifting his or her body's center of gravity that was also displayed. The target moved for a span of 15cm horizontally on the 14-inch screen, and also, in lateral and antero-posterior (horizontal and vertical) on CRT directions at a constant velocity of 0.125Hz. Sixty-seconds recordings are obtained. In BTT, the gain for target against tracking was fixed at 2.0 (target: tracking=1: 2). The target was 100cm anterior to the platform where the subject stood erect with the feet close together. The criteria for evaluation of the tracking function were determined by our preliminary study, titled “Index of BTT movement”, and was useful during our present study. These criteria were determined ranking to E from A. The A rank indicated best tracking. Determination of rankings were performed by good or not tracking line against target trace line on recorded papers. Age-dependent changes in scores were obtained and analyzed. Results suggested that the tracking ability started to deteriorate after age 40, and these differences were observed in lateral and antero-posterior (horizontal and vertical on CRT) directions for all age groups. Tried for a with 30 years old changes, increase of a rate that A ranking occupies with a lateral direction law fast stimulation BTT from 20-year-old changes though, didn't try for a significant difference with a anteroposterior direction law fast stimulation BTT. Try start were 50-year-old changes with an antero-posterior BTT, 40-year-old changes with a lateral BTT E ranking. C, D, rate that E ranking occupies increases consequently to become 80-year-old changes and advanced age from 60 years on. For the tendency, a small tendency tried for the rate for antero-posterior stimulation BTT compared with a lateral stimulation BTT. Whether thought about for this, an of direction is prompt nearly against an outside stimulation since it keeps a balance with standing and being mended.